Perspectives on Advance Care Planning and Palliative Care Among Adults with Congenital Heart Disease - Steiner, Jill M. (Congenit Heart Dis, 2018)
BACKGROUND: Patients with adult congenital heart disease (ACHD) report that advance care planning (ACP) is important, and that they want information about prognosis. However, recognizing importance and being willing to participate are different constructs, and how and when to begin ACP and palliative care discussions remains ill-defined. METHODS: We conducted a cross-sectional survey of 150 consecutive outpatients to assess willingness to participate in ACP, with whom, and important barriers and facilitators to these discussions. RESULTS: The majority of participants (69%) reported being willing to participate in ACP; 79% to have a meeting to discuss goals and care preferences; and 91% to speak to a clinician who specializes in palliative care. Being married and anticipating a shorter lifespan were associated with increased reported willingness to participate in ACP. The healthcare provider with whom most participants preferred to have these discussions was their ACHD clinician. Participants identified important barriers and facilitators to these discussions. CONCLUSION: Patients with ACHD report being willing to participate in ACP and palliative care discussions. Patients prefer to have these discussions with their ACHD clinicians, thus ACHD clinicians need to be prepared to address these issues as part of routine care.